2013
DOI: 10.1186/1756-3305-6-6
|View full text |Cite
|
Sign up to set email alerts
|

Field trial on a novel control method for the dengue vector, Aedes aegypti by the systematic use of Olyset® Net and pyriproxyfen in Southern Vietnam

Abstract: BackgroundJars, tanks, and drums provide favorable rearing/breeding sites for Aedes aegypti in Vietnam. However, the use of insecticides to control mosquitoes at such breeding sites has not been approved in Vietnam since they are also often sources of drinking water, making larval vector control difficult. Mosquito nets pre-treated with long-lasting insecticide treated nets (LLITNs) form an effective measure for malaria control. We examined changes in the abundance of immature Aedes aegypti to evaluate the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 36 publications
0
45
0
Order By: Relevance
“…Tackling the problem of human movement in dengue studies is more difficult because Aedes aegypti feeds during the day when people are engaged in their daily activities. Potential strategies to avoid this would be to use larger cluster areas or monitor epidemiological outcomes in a sentinel cohort that is less mobile (e.g., young children) [64]. Even if these steps are taken it is a good idea to collect travel histories from study participants, particularly if the intervention is located in a household.…”
Section: Selection Of Sites For Entomological Monitoringmentioning
confidence: 99%
“…Tackling the problem of human movement in dengue studies is more difficult because Aedes aegypti feeds during the day when people are engaged in their daily activities. Potential strategies to avoid this would be to use larger cluster areas or monitor epidemiological outcomes in a sentinel cohort that is less mobile (e.g., young children) [64]. Even if these steps are taken it is a good idea to collect travel histories from study participants, particularly if the intervention is located in a household.…”
Section: Selection Of Sites For Entomological Monitoringmentioning
confidence: 99%
“…Recently, as an example of insecticide-impregnated net-based technology, Kawada et al (2012) set the permethrin-impregnated net on the ceiling as a more effective methodology against malaria. Tsunoda et al (2013) reported a novel control method of using permethrin-impregnated nets as the lids over jars to control Aedes aegypti (L.). The combination of these methods proved to be effective for the control of malaria and dengue vector mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the increasing use of lethal ovitraps for Aedes control (Zeichner 2011), the success of nets impregnated with insecticides in controlling malaria (Rachavendra et al 2011), more recently evaluated in dengue control (Kroeger et al 2006;Lenhart et al 2008), and the use of controlled release formulations for mosquito larvae control (Nayar et al 2002;Seng et al 2006, Tsunoda et al 2013, our laboratory began to evaluate different natural materials such as stearin, paraffin and beeswax containing different amounts of pyriproxyfen as slow release formulations for A. aegypti control. In a previous work, hollow candles made of a paraffin/stearin mixture or beeswax containing 0.01 or 0.05 % pyriproxyfen and used as bioassay jars showed EI 100 % and residual activity of at least 1 year (Juan et al 2013).…”
Section: Introductionmentioning
confidence: 99%